Monitoring the safety of the adjuvanted human papillomavirus vaccine, HPV-16/18-AS04: Protocol for a cohort study using electronic health records in Yinzhou, China - Junting Yang; Sarah Welby; Zhike Liu; Siwei Deng; Guangxu Liu; Ruogu Meng; Yu Yang; Yixin Sun; Yunkun He; Ning Jiang; Zhenhua Wu; Keruo Liu; et al. (Taylor & Francis Group, 2024)
This protocol was developed to conduct population-wide surveillance of the bivalent HPV-16/18-AS04-adjuvanted human papillomavirus (HPV) vaccine in terms of uptake and safety outcomes including potential immune-mediated diseases (pIMDs) and pregnancy-related outcomes in China. The study will use electronic health records from 2010 to 2020 from the Yinzhou Regional Health Information Platform and include a population-based cohort of female permanent residents aged 9-45 years. Baseline and follow-up periods will be defined according to the 2017 introduction of HPV-16/18-AS04 in China. Patients with pIMDs and pregnancy-related outcomes will be identified using primary diagnostic codes from outpatient and inpatient electronic health records. A time trend analysis will be performed to describe the incidence of pIMDs and pregnancy-related outcomes during baseline and follow-up periods by age and overall, per calendar year. Depending on the number of safety outcomes and the size of the study population, incidence in vaccinated and unvaccinated cohorts will be compared using a Poisson regression model for pIMDs and a logistic regression model for pregnancy-related outcomes, adjusting for age and calendar year. Methods and findings from this study will provide valuable experience for designing future real-world studies and complement observations made during clinical trials and post-marketing studies.Study registration: http://www.chinadrugtrials.org.cn/index.html: CTR20210523.